(untitled) (Bangladesh Journal of Neuroscience, 2026)
Objective: To assess the association of long time sodium valproate therapy with non alcoholic fatty liver disease among epileptic patients. Method:It was a cross-sectional analytical study. Total 40 epileptic patients who had received valporic acid (VPA) monotherapy for at least one year were taken as case. Another 40 newly diagnosed age and sex matched epileptic patients without any antiepileptic drugs were also taken for comparison. Participants underwent hepatic ultrasound, anthropometric evaluations, and biochemical tests. Result: The occurrence of ultrasound-diagnosed non alcoholic fatty liver disease (NAFLD) was higher (37.5%) in VPA-treated patients than in controls (10%) with significant difference (P=.004). There was no significant difference in serum cholesterol level(165.60± 14.99 mg/dl vs.162.38 ± 11.74 mg/dl, P =.287), HDL level (42.83 ± 2.31mg/dl vs. 43.53 ± 2.51 mg/dl, P = .198), LDL level(99.6±13.43mg/dl vs. 96.65 ± 11.77mg/dl, P=.299) andtriglyceride level(116.9± 14.14 mg/dl vs 113.2 ± 10.32 mg/dl, P =.185) between valproate and non valproate group. The BMI of valproate treated patients were also higher (23.28±2.62) than the mean BMI of control group (21.27± 2.53) with significant difference (P=.001). The waist circumference was also higher in valproate treated patients (83.85±10.01cm vs. 78.55±9.95 cm) with significant difference (P=.020). Conclusion: Sodium valproate mono-therapy is associated with non alcoholic fatty liver disease among epileptic patients, who have typical VPA-related increased body weight.